Minimal Elements for the Prime Numbers. Issue 3 (2nd July 2016) - Bright, Curtis; Devillers, Raymond; Shallit, Jeffrey
ABSTRACT: We say a string of symbols s is minimal for a language L if s is a member of L, and it is not possible to obtain another member of L by striking out one or more symbols from s . Although the set M ( L ) of minimal strings is necessarily finite, determining it explicitly for a given L can be a difficult computational problem. We use some number-theoretic heuristics to compute M ( L ), where L is the language of base- b representations of the prime numbers, for 2 ≤ b ≤ 30.